Nucleotide and copy-number polymorphism at the odorant receptor genes Or22a and Or22b in Drosophila melanogaster. - Aguadé, M. (Molecular Biology and Evolution, 2009)
In Drosophila, odorant receptors are encoded by an old and moderately sized multigene family. Or22a and Or22b are two tandemly arranged genes of this family that have proved to be the result of a rather young duplication. Nucleotide variation in the region spanning both duplicates was surveyed in four natural populations (two African and two non-African) of Drosophila melanogaster and also analyzed in species of the melanogaster subgroup. The intraspecific survey revealed a particular copy-number polymorphism in some of the studied populations, with the two genes (Or22a and Or22b) present in the long variant and a single chimeric gene (Or22ab) present in the short variant. Estimated nucleotide diversity was higher in the short than in the long variant, despite the ancestral character of the latter variant in D. melanogaster. The general skew toward low-frequency variants detected in the non-African long variant and its reduced level of silent polymorphism relative to divergence is consistent with the recent fixation of an advantageous mutation at, or nearby, the Or22 long variant region. The nonnegligible frequency of the short variant and the presence of a highly divergent haplotype in the East African sample would point to direct or indirect selection for its maintenance in the species. There was evidence for a generally more rapid evolution of the Or22b copy at both synonymous and nonsynonymous sites. However, an excess of nonsynonymous substitutions was only detected in the early history of this copy.